Islamic Education for Religious Moderation and Cultural Identity among the Sasak Community - Baiq Mulianah; Dewi Puspita Ningsih; Galih Suryadmaja; Lalu Rohadi Rahman; Ahmad Fauzan; Andri Warseto (Edukasia Islamika : Jurnal Pendidikan Islam, 2026)
Studies on religious moderation in Islamic education have predominantly approached moderation as a normative educational outcome, while giving limited attention to local culture as a pedagogical mechanism through which religious values are interpreted, experienced, and internalized in everyday life. This study examines the internalization of religious moderation as a manifestation of wasatiyyah through Islamic education in the Sasak community. It develops an Islamic pedagogical model grounded in local culture for the digital age. Existing studies have largely discussed religious moderation within normative educational frameworks while paying limited attention to local culture as a pedagogical mechanism of value internalization. Using a qualitative descriptive-analytical approach, data were collected through literature review and non-participant observation in pesantren, majelis taklim, and socio-cultural settings across Lombok Island, and analyzed thematically and interpretively. The findings reveal that religious moderation is internalized through socio-cultural pedagogical processes embedded in everyday community life. The moral modelling, habituative pedagogy, experiential learning, symbolic pedagogy, hidden curriculum, and community-based learning mechanisms embedded in traditional practices such as begibung, nyongkolan, and awig-awig, as well as cultural performances such as Gendang Beleq, Rebana Gending, and Wayang Sasak, are internalized to instill tolerance, deliberation, social balance, and collective responsibility. The novelty of this study lies in the formulation of an Islamic pedagogical model grounded in local culture that integrates these mechanisms in a single framework. The model offers a culturally based approach to strengthening religious moderation in contemporary Muslim societies.